Serial Sections of Small Fossils. A New Method - Birket-Smith, Jørgen (Danmarks Geologiske Undersøgelse IV. Række, 1950)
An historical review of the practical study of foraminifera is followed by a selection of detailed accounts of methods for the study of the internal structure of foraminifera. The author’s technique for serially sectioning small fossils is presented in great detail. After embedding in celloidin the fossil material is dissolved, and replaced by paraffin wax which may, after microtoming, be removed, and the celloidin stained and embedded in dammar-xylene. This technique enables the finer detail of small fossils to be studied in transparency. Photographs of completed preparations, and a comprehensive bibliography are included.